INPSIRE può essere esportata? - Salvemini, Mauro (GEOmedia, 2009)
INSPIRE: could it be exported? As a European Directive, INSPIRE's approval process had to be political before than technical. This implies a great effort and participation for all the parts envolved in order to fully understand and evaluate all the aspects of the directive and all the upgrades it needs. The idea then is to export this decision process to other similar international contexts. In 2009, the american and asian-pacific committees voted a resolution that puts the INSPIRE directive as a reference point for similar future operations in those areas. This will allow INSPIRE to lead the activities in those regions, and at the same time gain experience on the development of SDI's abroad.